Stroke due to atrial fibrillation in a population-based stroke registry (Ludwigshafen Stroke Study) CHADS2, CHA2DS2-VASc score, underuse of oral anticoagulation, and implications for preventive measures - Palm, Frederick; Kleemann, T.; Martins dos Santos, Michael; Urbanek, Christian; Buggle, F.; Safer, Anton; Hennerici, Michael G.; Becher, Heiko; Zahn, R.; Grau, Armin J. (European journal of neurology, 2013)
Background and purpose Atrial fibrillation (AF) is amongst the most important etiologies of ischaemic stroke. In a population-based stroke registry, we tested the hypothesis of low adherence to current guidelines as a main cause of high rates of AF-associated stroke. Methods Within the Ludwigshafen Stroke Study (LuSSt), a prospective ongoing population-based stroke register, we analyzed all patients with a first-ever ischaemic stroke (FEIS) owing to AF in 2006 and 2007. We determined whether AF was diagnosed before stroke and assessed pre-stroke CHADS2 and CHA2DS2-VASc scores. Results In total, 187 of 626 patients with FEIS suffered from cardioembolic stroke owing to AF, which was newly diagnosed in 57 (31%) patients. Retrospective pre-stroke risk stratification according to CHADS2 score indicated low/intermediate risk in 34 patients (18%) and high risk (CHADS2 ≥ 2) in 153 patients (82%). Application of CHA2DS2-VASc score reduced number of patients at low/intermediate risk (CHA2DS2-VASc score 0-1) to five patients (2.7%). In patients with a CHADS2 score ≥ 2 and known AF (n = 106) before stroke, 38 (36%) were on treatment with vitamin K antagonists on admission whilst only in 16 patients (15%) treatment was in therapeutic range. Conclusions Our study strongly supports the hypothesis that underuse of oral anticoagulants in high-risk patients importantly contributes to AF-associated stroke. CHA2DS2-VASc score appears to be a more valuable risk stratification tool than CHADS2 score. Preventive measures should focus on optimizing pre-stroke detection of AF and better implementation of present AF-guidelines with respect to anticoagulation therapy.
First published: 12 July 2012
Im Titel ist die Ziffer "2" jeweils tiefgestellt
Gesehen am 16.12.2021